Job Choice with Multi-Criteria Decision Making Approach in a Fuzzy Environment - ALP, Selçuk; ÖZKAN, Tuğba KIRAL (International Review of Management and Marketing, 2015)
One of the most important decisions that a fact in individual's life is job choice. Job choice can be defined as opting for the optimum type of entity one can practise his profession among the businesses that exist in a society. In this study, job choice problem is considered as a multi-criteria decision making problem and it has been analyzed by using Fuzzy TOPSIS method; one of the multi-criteria decision making methods. 275 surveys have been carried out in total for 7 different job choice criteria determined (wage level, job security, location of the business, vested benefits, respectability in the society, the difficulty level of the business, flexible working time opportunity) and 4 different types of entity choice alternative (public corporation, special purpose entity, foreign capital enterprises, one's own business). As a result of the analysis, it has been found that in general, the preferred job choice criteria of the decision makers (the individuals who participated in the survey) is respectively as follows; the respectability level of the business in the society, wage level, and flexible working time opportunity. Thus, these criteria have been considered more important when compared with other criteria. It has also been determined that the type of entity choices in which the decision makers wish to work are listed respectively as foreign capital enterprises, in one's own business as an enterpreneur, public corporation and lastly special purpose entity. Moreover, the decision makers have been grouped as regards to the types of each entity and the fields they have worked in and similar analysis have been carried out and the results obtained have been evaluated. Keywords: Fuzzy TOPSIS; Job Choice; Multi-Criteria Decision Making JEL Classifications : C61; J2